Clinical Features and Prognosis of Primary Epithelial-Myoepithelial Carcinoma of Salivary Gland: A Surveillance, Epidemiology, and End Results Database-Based Study - Hui Han MD; Li-Na Pan MD (Cancer Control)
Objective The clinical characteristics and prognosis of primary epithelial-myoepithelial carcinoma of salivary gland (EMC-SG) have not been defined well due to its rarity. The purpose of this study is to assess the proportion of EMC-SG among salivary gland cancers, describe the clinicopathological features and prognosis of this disease, further analyze the factors associated with EMC-SG survival, and establish individual survival-predicting models. Methods Data on patients diagnosed with salivary gland malignancy between 2000 and 2020 were collected from the Surveillance, Epidemiology, and End Results database. The Kaplan-Meier method and log-rank test were employed to estimate survival of EMC-SG patients. Univariable and multivariable Cox proportional hazards models were developed to determine the EMC-SG survival-associated factors. Furthermore, EMC-SG nomograms were constructed. Results A total of 15 212 patients with salivary gland malignancy were identified. Of these, 310 cases were diagnosed with EMC-SG, representing a prevalence of 2.03% (95%CI 1.82%-2.28%). The overall survival (OS) rates for all 310 EMC-SG patients at 2-year, 5-year, and 10-year were 92.43%, 84.85%, and 73.39%, respectively. Age, primary site, and T stage were independent prognostic factors for OS, while pathological grade and the use of surgery were independent prognostic factors for cancer-specific survival (CSS). The concordance index (C-index) for the OS- and CSS-specific nomograms was 0.72 (95%CI 0.64-0.80) and 0.77 (95%CI 0.67-0.87), respectively. The calibration curve and receiver operating characteristic analysis demonstrated that the predicted values aligned well with the actual observations. Decision curve analysis indicated the superiority of the nomograms over the traditional Tumor Node Metastasis staging system. Conclusions This study represents the largest cohort of EMC-SG patients used to investigate the characteristics and prognosis of this disease. EMC-SG patients often have a less aggressive course and favorable prognosis. The established nomograms provide a useful tool for clinicians to predict patient outcomes, and can assist in customizing the counseling approach for this rare disease.